Agaricus subrufescens in México: an edible, medicinal, and potentially cultivable non-wood forest resource - Velázquez-Narváez, Alberto Carlos; Medel, Rosario; Mata, Gerardo; Espinosa de los Monteros, Alejandro (Instituto de Ecología, A.C., 2018)
Agaricus subrufescens is an edible fungus with medicinal properties which is cultivated with commercial aims in several countries; in nature, it has a wide distribution almost worldwide. This species has not been recorded in the wild for Mexico, thereby herein it was morphologically and molecularly characterized for the first time from a wild collection coming from the cloud forest in the central part of the State of Veracruz, Mexico. In addition, a strain was isolated from the collected specimen, which was grown. In this study, we confirm the occurrence of A. subrufescens in Mexico, being the southernmost collection in North America, and it is proposed as a forest, non-timber, and potentially cultivable species.